Cu Nanoclusters with Aggregation Induced Emission Enhancement. Issue 22 (13th May 2013) - Jia, Xiaofang; Li, Jing; Wang, Erkang
Abstract A facile and versatile method for preparing water‐soluble, stable, luminescent Cu nanoclusters (NCs) via the process of size‐focusing etching from nonluminescent nanocrystals is presented. Using glutathione as a model ligand, the smallest cluster, Cu2, is selectively synthesized to form a nearly monodisperse product, eliminating the need for tedious size fractionation. Evolution of photoluminescence and absorption spectra reveal that the formation of stable cluster species occurs through surface etching. Intriguingly, the as‐prepared CuNCs exhibit an aggregation‐induced emission enhancement effect. The CuNCs emit a faint light when dispersed in aqueous solution, but generate a striking fluorescence intensity enhancement upon aggregation. Armed with these attractive properties, the emissive CuNCs are expected to open new opportunities for the construction of light‐emitting diodes, chemosensors, and bioimaging systems.